VOICE-ENABLED REMOTE SURVEILLANCE SYSTEM - Jitendra Bhandarkar,; Gouri Halde,; Sunita Parihar, (International Journal of Innovations in Engineering Research and Technology, 2023)
In this particular undertaking, the objective is to create a live video streaming system intended for remote surveillance purposes. With the increasing popularity of video surveillance systems, the ability to monitor an entire system from a distant location has become both intriguing and convenient. This project focuses on the development of an embedded, real-time surveillance system utilizing the ESP32 Cam module. The system encompasses various features including intrusion detection through face detection and recognition, fire detection, voice notifications, live video streaming, and portability. The proposed solution presents an economical, voice-guided, and universally accessible surveillance approach that is both effective and straightforward to implement.